AN ANALYSIS OF STUDENTS’ PERCEPTION TOWARD INSTAGRAM USING IN LEARNING WRITING OF TENTH GRADE STUDENTS AT SMK PGRI 2 GIRI BANYUWANGI IN ACADEMIC YEAR 2021/2022 - Sutami Dwi Lestari; Yuli Sugianto; Shannava Putri Shyhab Shanaz (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
Writing is a form of communication between the writer who express the idea and the reader who comprehends what they read. However writing is a very difficult and complex process. It requires some important skills to make the sentence which clear and acceptable. Nowadays, the use of social media for learning is a new phenomenon. One of the social media is Instagram. Instagram is a social network based on sharing pictures and videos which can be posted to other social media sites. Instagram has also many features that can be useful for students. This research aimed to analysis students’ perception toward Instagram using in learning writing. The research design was descriptive qualitative. The respondents were 20 students in SMK PGRI 2 Giri Banyuwangi which determined by using purposive sampling. The data were taken by using questionnaire and interview. The data from questionnaire analyzed Likert Scale, while the data from interview by interviewed. The respondents for questionnaire were 20 respondents, while interview were 3 respondents. The data analysis was determined based on theory of five indicators. The percentage results of indicator are sharing information (66%), social interaction (66%), communicative utility (68%), self-expression (69%), and entertainment (66%). Analysis of interview by 3 respondents by English teacher, they agree that Instagram become media for support learning writing. Based on the result above, it was concluded that students and also teacher agree using Instagram for learning writing.